The importance of considering temporal intraspecific trait variation in Campos grasslands - Caram, Nicolas; Casalás, Felipe; Wallau, Marcelo O.; Sollenberger, Lynn E.; Soca, Pablo; Cadenazzi, Mónica; Boggiano, Pablo (Journal of vegetation science, 2024)
Aims Changes in species composition and intraspecific trait variation are recognized as potential drivers of population and community temporal dynamics but their independent and overlapping effects have not been distinguished conclusively. Our goal was to quantify the relevance of temporal vs spatial changes in species composition and intraspecific trait variations when assessing community responses to seasonality, grazing pressure and above‐ground biomass gradients. Location Campos grassland in northeastern Uruguay. Methods Leaf dry matter content, specific leaf area, leaf width and tensile strength of dominant grass species were assessed across summer–autumn, winter, and spring seasons, under two grazing pressures. Species composition and above‐ground biomass were estimated in 20 × 20‐cm permanent quadrats within each season. Species trait variability was decomposed across space and time using hierarchical linear mixed models, while the spatio‐temporal community functional variation was decomposed into species turnover (abundance and/or species identity shifts) and intraspecific trait variation. Additionally, we explored the relevance of including or not including temporal intraspecific trait variation on community responses to seasonality, above‐ground biomass and grazing pressure using linear mixed models. Results Intraspecific trait variation explained 22.4%–66.5% of total trait variability, and it was generally more important across time than space, which accounted for 12.2%–57.7% of total variability. The within‐species trait variability was generally more important than species turnover in explaining the community spatio‐temporal functional variation. In general, seasonality more strongly caused intraspecific changes while the above‐ground biomass gradient caused species turnover. Functional community responses to grazing pressure, above‐ground biomass and seasonality were affected by considering or not considering intraspecific trait variation. Conclusions Trait variation within species across seasons is at least equally important as variation within species across space. Its influence in the functional changes of vegetation should not be considered only along environmental gradients but also through time. Intraspecific trait variation through seasons was at least equally important as variation within species across space and explained a significant variability of the community spatio‐temporal functional variation. The inclusion of temporal traits variability determined different significances and estimates when testing functional community responses to environmental filters in a short gradient grassland.